2007
DOI: 10.1021/np078002l
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene Glycosides from the Flower Petals of Sunflower (Helianthus annuus) and Their Anti-inflammatory Activity

Abstract: Two new oleanane-type triterpene glycosides, named helianthosides 4 (4) and 5 (5), along with four known triterpene glycosides, helianthosides 1 (1), 2 (2), 3 (3), and B (6), were isolated from an n-butanol-soluble fraction of a methanol extract of sunflower (Helianthus annuus) petals. The structures of the two new compounds were determined on the basis of spectroscopic and chemical methods. Upon evaluation of compounds 1-6 for inhibitory activity against 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…The anti-inflammatory activity of these compounds has been demonstrated to be closely parallel with that of the inhibition of DMBA-TPA papilloma formation in the mouse-skin model (Yasukawa et al, 1996), and hence the oleanolic acid derivatives tested in this study might be expected to possess high antitumor-promoting effect in the same animal model. The high anti-inflammatory activities of various types of triterpene acids Banno et al, 2004Banno et al, , 2006Manosroi et al, 2013) and oleanane-type triterpene glycosides (Manosroi et al, 2013;Ukiya et al, 2006Ukiya et al, , 2007 have also been observed in our previous studies.…”
Section: Anti-inflammatory Activity Against Tpa-induced Inflammation supporting
confidence: 77%
“…The anti-inflammatory activity of these compounds has been demonstrated to be closely parallel with that of the inhibition of DMBA-TPA papilloma formation in the mouse-skin model (Yasukawa et al, 1996), and hence the oleanolic acid derivatives tested in this study might be expected to possess high antitumor-promoting effect in the same animal model. The high anti-inflammatory activities of various types of triterpene acids Banno et al, 2004Banno et al, , 2006Manosroi et al, 2013) and oleanane-type triterpene glycosides (Manosroi et al, 2013;Ukiya et al, 2006Ukiya et al, , 2007 have also been observed in our previous studies.…”
Section: Anti-inflammatory Activity Against Tpa-induced Inflammation supporting
confidence: 77%
“…Furthermore, because RL-TGR seems to be specifically expressed in fish, this coreceptor in fish might have coevolved with the triterpene glycoside compounds found in their potential prey organisms. Triterpene glycosides are closely related to steroidal glycosides and saponins, which are found in a variety of marine and terrestrial organisms (20,30,31,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Thus, RL-TGR and related receptors might serve as detectors of these classes of compounds, and other RAMP-like coreceptors might have evolved as detectors of other chemical defenses.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Ukiya et al found that methanol extracts of HAF markedly inhibited TPAinduced inflammation in mice. 40,42 Here, we hypothesized that HAF possesses photoprotective ability against UVBinduced damage. As expected, our results demonstrated that HAF effectively reversed UVB-induced photoaging by inhibiting MMP secretion and procollagen type I reduction, which were involved in inactivating MAPK/AP-1 and upregulating TGF-β expression.…”
Section: Discussionmentioning
confidence: 99%